1998
DOI: 10.1023/a:1023056804548
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The human embryo shows paternal centrosome inheritance and perpetuation like most other animals. Inheritance of defective centrosomes may lead to abnormal cleavage and contribute to infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The evidence that elongated radial sperm aster was involved in the movement and apposition of male and female pronuclei of buffalo's zygote suggested that the centrosomal material is primarily paternally inherited and is similar to previous reports in other mammalian species such as human [1, 2], sheep [3], rabbit [4], porcine [5], bovine [68], and rhesus monkey [9]. However, this is different in mouse because cytoplasmic microtubules in the cytoplasm originate from maternal centrosomes and sperm astral microtubules were not detected in the decondensing paternal chromatin [10, 41].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The evidence that elongated radial sperm aster was involved in the movement and apposition of male and female pronuclei of buffalo's zygote suggested that the centrosomal material is primarily paternally inherited and is similar to previous reports in other mammalian species such as human [1, 2], sheep [3], rabbit [4], porcine [5], bovine [68], and rhesus monkey [9]. However, this is different in mouse because cytoplasmic microtubules in the cytoplasm originate from maternal centrosomes and sperm astral microtubules were not detected in the decondensing paternal chromatin [10, 41].…”
Section: Discussionsupporting
confidence: 85%
“…The microtubules actively involve in the process of fertilization by the formation of microtubule networks that facilitate the migration and apposition of male and female pronuclei. These microtubules are paternally inherited in most mammalian species, including human [ 1 , 2 ], sheep [ 3 ], rabbit [ 4 ], porcine [ 5 ], bovine [ 6 8 ], and rhesus monkey [ 9 ]. On the other hand, the paternal centrosome in the ooplasm is functionally absent in mice, and thus the syngamy of the two pronuclei requires the maternal centrosome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sperm centriole duplicates during the pronuclear stage and separates after syngamy to serve as the mitotic center from the first cleavage division up to the blastocyst stage [27, 28]. During that period the maternal centrosome is not functional [29]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be related to incomplete DNA replication and the consequently high frequency of chromosomal abnormalities, as observed in human and bovine embryos [11,18]. The cause of direct cleavage is the formation of tripolar or tetrapolar spindles, which is associated with the abnormal distribution of chromosomes in the blastomeres [18,19]. The most frequently occurring abnormality observed in human IVF embryos is the fragmentation of the cytoplasm [4,8].…”
Section: Discussionmentioning
confidence: 99%